Molecular phylogenetic relationships and implications for the circumscription of Colchicaceae (Liliales). (7th May 2013) - Nguyen, Thi P. A.; Kim, Jung Sung; Kim, Joo‐Hwan
<x xml:space="preserve">Abstract</x> Colchicaceae (Liliales) comprise c. 250 species and 15–21 genera of rhizomatous or cormous perennials and are distributed through temperate and tropical Africa, Europe, Asia and North America. They have been traditionally divided into two subfamilies, but this division is still unclear and the phylogenetic relationships among members of the family and the sister relationships of the family have been debated. Moreover, it is uncertain whether the expanded circumscription of Colchicum, Gloriosa and Wurmbea to include Androcymbium, Littonia and Onixotis plus Neodregea, respectively, is unavoidable. In this study, sequences of three plastid genes, atpB, matK and rbcL, were analysed to reconstruct phylogenetic relationships in Colchicaceae. The matK region was the most variable and provided the most potentially parsimony‐informative sites. We also conducted molecular phylogenetic analyses using the combined data with sequences for three non‐coding regions generated by Vinnersten and Reeves. Our results strongly support the monophyly of Colchicaceae and the redefined circumscription to include two subfamilies, Wurmbeoideae and Uvularioideae. The Uvularia‐Disporum clade, i.e. Uvularioideae, is sister to the rest of Colchicaceae and differentiated from Burchardia, previously suggested to be sister to the rest of Colchicaceae. In our analysis, Burchardia is placed in Wurmbeoideae. A close relationship between Tripladenia and Schelhammera was strongly supported and these are transferred to Wurmbeoideae from Uvularioideae. The six tribes sensu Vinnersten and Manning were shown to be monophyletic. Our results support the expanded circumscription of Colchicum (including Androcymbium) and Gloriosa (including Littonia), but the circumscription of Wurmbea and related genera requires further study. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 172, 255–269.